Considering the Self in the Link Between Self-Esteem and Materialistic Values: The Moderating Role of Self-Construal - Zhang, Yan; Hawk, Skyler T. (Frontiers in Psychology, 2019)
Studies consistently show that materialism might be a strategy people use to cope with low self-esteem. This link might differ among people holding different definitions of the self in terms of the relationship with others, however. This research re-examined the link between self-esteem and materialistic values from the perspective of how people define the self, or their self-construal. In three studies, we explored the moderating role of self-construal in the link between Chinese participants’ self-esteem and materialistic values. Through a self-report survey (Study 1, N = 422), experimental manipulation of self-construal (Study 2, N = 151), and experimental manipulation of both self-esteem and self-construal (Study 3, N = 123), results indicated that self-esteem and self-construal interacted in predicting materialistic values. Specifically, self-esteem negatively predicted materialistic values when interdependent self-construal was low, but not when it was high. We suggest that individuals’ pursuit of materialism under conditions of low self-esteem might depend on how they define the “self”.